Ecosystem Effects of Morphological and Life History Traits in Two Divergent Zooplankton Populations - Karlsson, Konrad; Winder, Monika (Frontiers in Marine Science, 2018)
Little is known about the ecosystem effects of locally adapted populations. The filter feeding copepod Eurytemora affinis is an abundant and important zooplankton in coastal waters that consist of a cryptic species complex with locally adapted populations. We used a mesocosm setup to investigate population and ecosystem interactions of two populations from the Baltic Sea with different morphology and life history traits. One population is laterally wider, larger-sized, more fecund, and have higher growth rate than the other. The experimental ecosystems varied in algae community (pelagic algae, and pelagic algae + benthic diatoms) with two resource supply scenarios. Results showed that the large-sized population is a more effective grazer. In low resource supply the small-sized population starved, whereas the large-sized population was unaffected, resulting in a larger population increase of both nauplii and copepodites than for the small-sized population. Addition of benthic diatoms to the pelagic algae community had much more negative effects on the reproduction of the large-sized population. This suggests that the large-sized population feed near benthic to a greater extent than the small-sized population, and that filamentous benthic diatoms interfere with the grazing process. Despite the negative effects of benthic diatoms, the large-sized population could maintain similar or higher reproduction than the small-sized population. In addition, the high grazing efficiency of the large-sized population resulted in a different community composition of algae. Specifically, flagellated species and small sized benthic diatoms were more grazed upon by the large-sized population. Our results show that morphologically divergent, yet phylogenetically closely related zooplankton populations can have different ecosystem functions, and in turn have different population increase in response to resource supply and algae community.